DOUBLED HAPLOIDS TECHNOLOGY IN PLANTS - Urazaliyev , K.R. (Eurasian Journal of Applied Biotechnology, 2015)
Regeneration of gametic cells to produce haploid or doubled haploid plants is an excellent example of totipotency of plant cells, called gametogenesis. Producing doubled haploid plants through androgenesis or gynogenesis facilitates the possibility of obtaining homozygous plants in a single step (one year). This approach is useful in plant breeding, genetic manipulation, and in many areas of basic research related to the study of plant biology. Achievement of homozygosity in one generation helps reduce the number of inbreeding cross cycles that are required to obtain purebred lines. As an effective system of plant regeneration, gametic cells also are preferred for breeding, genetic transformation, transgenic plant research, and other regeneration efforts. Doubled haploid plants and the obtained homozygous lines are used in several areas of basic research such as classical plant genetics and cytogenetics, modern molecular genetics, including induced mutagenesis, site-directed mutagenesis, genome mapping and the evaluation of the relative remoteness of genomes, gene dosage effects, and the analysis of the relationships mechanisms of genetic control of chromosome pairs. One of the most important areas of practical application of this technology is plant breeding. Many plant species have the ability to regenerate from microspores. However, in most cases, it is necessary to perform one or more pre-processing steps, in the form of physical, physiological and/or chemical treatments. Pre-processing must be used to switch microspores from a gametophytic development pathway to a sporophytic development path. It is possible to increase the efficiency of this process by the direct, artificial manipulation of individual microspores, which has enabled the successful production of regenerated plants in more than 300 species.